Enrolled nurse transition : development of a university preparation program for direct entry to second year : final report. - Logan, Patricia; Cox, Jennifer; Anderson, Judith; van Reyk, David; Hillman, Elspeth; Johnston, Amy; Salvage-Jones, Judith (Australia. Dept of Education and Training (DET), 2018)
Every year, hundreds of enrolled nurses (ENs) commence pre-registration degrees in over 30 tertiary institutions across Australia. The knowledge and expertise that registered nurses (RNs) bring to their workplace is critical in maintaining the standard of care for patients in hospitals and health facilities, community health centres, defence forces, primary and secondary industries, insurance and workplace health and safety. Our goal is to increase the level of support for EN transitioning to an RN degree. We want them to be prepared, confident and, most of all, inspired in their first year. We also want to increase the level of support for anyone who teaches ENs. [Executive summary, ed]